Benchmarking principal component analysis for large-scale single-cell RNA-sequencing - Tsuyuzaki, Koki; Sato, Hiroyuki; Sato, Kenta; Nikaido, Itoshi (Genome Biology, 2020)
Background Principal component analysis (PCA) is an essential method for analyzing single-cell RNA-seq (scRNA-seq) datasets, but for large-scale scRNA-seq datasets, computation time is long and consumes large amounts of memory. Results In this work, we review the existing fast and memory-efficient PCA algorithms and implementations and evaluate their practical application to large-scale scRNA-seq datasets. Our benchmark shows that some PCA algorithms based on Krylov subspace and randomized singular value decomposition are fast, memory-efficient, and more accurate than the other algorithms. Conclusion We develop a guideline to select an appropriate PCA implementation based on the differences in the computational environment of users and developers.